2020
DOI: 10.1007/s12144-020-01008-4
|View full text |Cite
|
Sign up to set email alerts
|

Mindsets matter for teachers, too: Growth mindset about teaching ability predicts teachers’ enjoyment and engagement

Abstract: Research on mindsets have mostly focused on students' beliefs about the malleability of their intelligence. However, past studies have not explored how teachers' beliefs about the malleability of their teaching ability is associated with teaching emotions and work engagement. Akin to intelligence mindsets, teachers might also hold either a fixed or growth mindset towards their teaching ability. We tested a model wherein teachers' emotions (i.e., enjoyment, anger, and anxiety) mediated the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 17 publications
2
22
0
3
Order By: Relevance
“…This finding connects to recent studies on the impact of teachers' mindsets on their teaching and, consequently, students' learning (e.g. Frondozo et al, 2020). Our insights add to the current SSI-based research on teachers' motives (e.g.…”
Section: Preparation Of the Lessonssupporting
confidence: 88%
“…This finding connects to recent studies on the impact of teachers' mindsets on their teaching and, consequently, students' learning (e.g. Frondozo et al, 2020). Our insights add to the current SSI-based research on teachers' motives (e.g.…”
Section: Preparation Of the Lessonssupporting
confidence: 88%
“… Zeng et al (2019) found out that teachers with the growth mindset experience enjoyable challenges, and they found out that wellbeing and incremental mindset act as mediator variables in the correlation between enjoyment and work engagement. Frondozo et al (2020) also stated that teachers’ growth mindset about their instructional capability is significantly correlated with their enjoyment and work engagement. They argued that instructors with a growth mindset in the instructional process usually regard teaching as a flexible job, and they assume activities as chances to improve their capabilities, and this results in enjoyment and work engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, it is important to note that growth mindset relates to increased job satisfaction. 51 When employees derive high meaning and deep enjoyment from their work, they will experience more living a calling. In sum, individuals who endorse the belief that a successful career can be developed and that they can achieve their future career goals are more likely to feel they are actually living out their calling than those who believe careers are destined.…”
Section: Growth Mindset About Work and Living A Callingmentioning
confidence: 99%